RANCANG BANGUN E-LIBRARY SMK NEGERI 1 SLAWI - Indah Puspita Mutiara; Sri Huning Anwariningsih; Dahlan Susilo (JURNAL GAUNG INFORMATIKA, 2014)
SMK Negeri 1 Slawi is one of the schools that have implemented an IT technology. With the growth with information and technology which increases rapidly and the increase of Internet users make SMK Negeri 1 Slawi must use a learning media. One way to solve the problem is by making E-library. The purpose of the Elibrary is to complete the existing traditional library and develop students science.